Metallophilic Interactions in Bimetallic Cyclometalated Platinum(II) N‐Heterocyclic Carbene Complexes. Issue 30 (30th June 2021) - Pinter, Piermaria; Soellner, Johannes; Strassner, Thomas
Abstract: Platinum(II) complexes with rigid and electron donating ligands are efficient phosphorescent emitters at room temperature. However, the excited‐state lifetimes of these complexes are, in general, relatively long. This problem, which can result in the degradation of the emitter, can be overcome by exploiting the natural tendency of platinum to form metallophilic interactions and aggregates. Herein, we report platinum(II) bimetallic complexes with 100 % quantum yield and at the same time exceptionally short radiative decay times, which in some cases are up to a hundredfold faster than the analogous monometallic complexes. Abstract : Bimetallic platinum(II) complexes with cyclometalated N‐heterocyclic carbene C ∧ C * ligands are among the fastest triplet emitters and at the same time show an unitary quantum yield.